2D speckle tracking echocardiography for the assessment of regional contractile reserve after myocardial infarction. Issue 5 (May 2016) - Szymczyk, Ewa; Lipiec, Piotr; Michalski, Błażej; Szymczyk, Konrad; Shim, Ahmed; Woźniakowski, Bartłomiej; Rotkiewicz, Arkadiusz; Stefańczyk, Ludomir; Kasprzak, Jarosław D.
Abstract : Aims: To assess whether quantitative resting assessment of local myocardial function by 2D speckle tracking echocardiography may be helpful for the evaluation of myocardial viability in patients after ST-elevation myocardial infarction (STEMI) and for the prediction of left ventricular function recovery after 12-month follow-up. Methods: The study group comprised 96 patients with first STEMI treated with successful primary percutaneous coronary intervention. Seven to 12 days after STEMI, all patients underwent resting echocardiography and low-dose dobutamine stress echocardiography (LDDSE) with visual assessment of contractile reserve which was the reference method for the evaluation of myocardial viability. After 12 months resting echocardiography with visual assessment of functional recovery was performed. Subsequently, acquired images were analyzed off-line using 2D speckle tracking echocardiography algorithm. Measurements included peak systolic longitudinal and transverse strain (SLS/STS), peak longitudinal and transverse strain (PLS/PTS), systolic longitudinal and transverse strain rate (SLSR/STSR) at baseline and after 12 months. Results: All analyzed longitudinal parameters of strain had a very good diagnostic value, while transverse parameters had only good diagnostic value for predicting myocardial viability defined on the basis of LDDSE. Moreover, SLS and PLS had good, whereas SLSR only satisfactory diagnostic value for predicting function recovery after 12-month follow-up. Conclusions: 2D speckle tracking analysis applied during resting echocardiography can be helpful for the prediction of myocardial viability and functional recovery in patients after STEMI. Longitudinal strain parameters allow the prediction of local contractile reserve with SLS showing best correlation with DSE results functional recovery after 12-month follow-up.